Aspectos florístico e estrutural de um fragmento de floresta com araucária utilizado para o pastoreio de bovinos - Watzlawick, Luciano Farinha (2002)
The aim of this paper was to know, analyze and describe the floristic composition of the shrub and tree component and the structure of a Montane Mixed Ombrophylous Forest Fragment, used for bovines pasturage, in the municipal district of Criúva - RS. It was inventoried 533 individuous in seven 10 x 100 m plots with DBH³ 10 em, distributed in 38 species from 33 gender and 20 families. The families wich presented the widest number of individuous were: Myrtaceae (33,0 %), Euphorbiaceae (19,7 %) e Araucariaceae (17,4 %). The total density found was 761,4 individuous/ha, and the medium DBH is 22,9 em and the higest 9,7 m. The part of the forest investigated is characterized by the lack of understorey, probably caused by intense presence of cattle, damaging especially plants of minor height and diameter. This fact might explain the lack of individuais to occupy the gaps caused by the removal of dominant trees out of the forest.